Type 1 IGF receptor associates with adverse outcome and cellular radioresistance in paediatric high-grade glioma - Simpson, Aaron D.; Soo, Ying Wei Jenetta; Rieunier, Guillaume; Aleksic, Tamara; Ansorge, Olaf; Jones, Chris; Macaulay, Valentine M. (British journal of cancer, 2020)
High-grade glioma (HGG) is highly resistant to therapy, prompting us to investigate the contribution of insulin-like growth factor receptor (IGF-1R), linked with radioresistance in other cancers. IGF-1R immunohistochemistry in 305 adult HGG (aHGG) and 103 paediatric/young adult HGG (pHGG) cases revealed significant association with adverse survival in pHGG, with median survival of 13.5 vs 29 months for pHGGs with moderate/strong vs negative/weak IGF-1R ( p = 0.011). Secondly, we tested IGF-1R inhibitor BMS-754807 in HGG cells, finding minimal radiosensitisation of 2/3 aHGG cell lines (dose enhancement ratios DERs < 1.60 at 2–8 Gy), and greater radiosensitisation of 2/2 pHGG cell lines (DERs ≤ 4.16). BMS-754807 did not influence radiation-induced apoptosis but perturbed the DNA damage response with altered induction/resolution of γH2AX, 53BP1 and RAD51 foci. These data indicate that IGF-1R promotes radioresistance in pHGG, potentially contributing to the association of IGF-1R with adverse outcome and suggesting IGF-1R as a candidate treatment target in pHGG.